Efeitos adversos causados pelo esquema de tratamento básico da tuberculose em um hospital universitário de referência no tratamento de tuberculose - MONTEIRO, Edinelson Rodrigues (2019)
Introduction: Tuberculosis is a globally occurring infectious disease and is currently considered a public health problem. The treatment is performed with four drugs in the first two months, and the drugs in the next four months, both with fixed fixed doses combined. Despite their effectiveness, these drugs can cause adverse effects, which may imply in the control of tuberculosis. Objective: To describe the adverse effects caused by the basic tuberculosis treatment scheme recommended by the Brazilian Ministry of Health. Methods: Retrospective, cross-sectional study of medical records of tuberculosis patients treated with the basic regimen at the João de Barros Barreto University Hospital, in Belém, Pará, in the period of 2015 and 2016. The statistical data were presented through absolute and relative frequencies. Results: The sample included 198 patients, being (53.54%) male. Age ranged from 10-89 years, with a predominance of 40-49 (21.71%) years and a mean age of 43 ± 17.3 years. There was a predominance of patients coming from Belém with (67.67%). About (59.1%) had one or more comorbidities. Of the total number of patients, (80.3%) were new cases, the isolated pulmonary form was the most diagnosed (63.14%) of the cases. There were adverse effects in (48.9%) patients. The frequency of minor adverse effects was (87.82%), and that of the greater effects of (12.18%). The gastrointestinal and cutaneous involvement were the most frequent (48.74% and 37.05%, respectively). Adverse effects were more prevalent in the first month of treatment (36.55%). In 9.6% of the patients, there was a need to change the therapeutic regimen, and of these, (73.68%) due to drug hepatitis. About (11.61%) abandoned treatment. Conclusion: The adverse effects rates with the current treatment regimen were similar to those found in treatment I. The highest frequency of adverse events occurred within the first month of treatment. Treatment abandonment occurred at a high frequency, and it was necessary to devise strategies to reduce it. Only in a small number of patients was there a need to change the therapeutic regimen. Given the relevance of the topic, prospective studies in this sense are necessary.